GAMBARAN PENGETAHUAN, SIKAP, DAN PERILAKU MENGENAI HIV/AIDS PADA SOPIR PARIWISATA DI DENPASAR - Pratiwi, Ni Komang Dewi Trisia; Suindrayasa, I Made; Pramitaresthi, I Gusti Ayu (Coping: Community of Publishing in Nursing; Vol 9 No 1 (2021): Februari 2021DO - 10.24843/coping.2021.v09.i01.p11, 2021)
The tourism drivers are categorized to be one of the groups which is at risk of HIV/AIDS infection. HIV/AIDS has a bad prognosis and can cause death. Therefore, the prevention of HIV/AIDS spread is needed. The importance of having knowledge about HIV/AIDS and being able to behave properly is a preventive effort that can be done by tourism drivers from the infection risk of HIV/AIDS. The aims of this study is describing the knowledge, attitude, and behavior related to HIV/AIDS of the tourism drivers in Denpasar. This study uses a descriptive method and a purposive sampling technique with the number of sample is 106 people. The result of the study shows that the majority of the male tourism drivers are 101 people; the average age is 38 years old; their last education is senior high school (71.7%) in majority, the 86 of them are married; moreover, they have worked on average for 11 years. The majority of the tourism drivers are categorized have good knowledge of the HIV/AIDS (51.9%). There are 56 drivers who have a positive attitude towards the HIV/AIDS (52.8%). Furthermore, there are 42.5% of the tourism drivers who own risky behavior for the HIV/AIDS infection. Based on this result, the other researchers are expected to conduct further studies related to the factors which influence the behavior which is at risk for the HIV/AIDS affection owned by the tourism drivers in Denpasar; moreover, the health institute is expected to conduct the HIV/AIDS checks for them.